Controle de Fusarium oxysporum f. sp. vasinfectum em algodoeiro com Trichoderma spp. - Holanda, Guilherme Chaves de (2022)
Fusarium oxysporum f. sp. vasinfectum (Fov) is a saprophytic fungus that can cause wilting, vascular browning and death of cotton plants. Fov presents efficient forms of survival through resistance structures, colonization of woody tissue and association with seeds. In turn, the use of high quality sanitary seeds is essential for high productivity and keeping the field healthy. Because Fov has the ability to survive in adverse conditions, disease management is a challenge and the use of synthetic fungicides has low efficiency. Management using biological control agents is an efficient alternative. Among the agents, fungi of the genus Trichoderma are used as antagonists to phytopathogens and generate an increase in the physiological aspects of the plant. The objective of this work was to evaluate Trichoderma spp. in control of Fov. He performed the isolation of Trichoderma spp. in soils of cotton producing areas. To conduct the experiments, treatments were used consisting of seven different isolates of Trichoderma spp., (02, 06, 11, 12, TS, TH and 729), fungicide Captana, control with the pathogen and absolute control. The Fov used was the CNPA 007 isolate from Embrapa Algodão. It carried out, in vitro, a double culture test, thermostable volatile, non-volatile and non-volatile metabolites, inhibition of conidia germination and mycoparasitism. Cotton seeds were obtained from producers in the municipality of Ingá and their sanitary and physiological quality was evaluated using the Blotter test, germination and emergence test. The biological control was carried out in a greenhouse and evaluated plant height, stem diameter, root length, dry matter, chlorophyll a and b index, chlorophyll a fluorescence and gas exchange in cotton plants. In the double culture test with simultaneous inoculation, the treatments inhibited 47% of the mycelial growth of the pathogen. In volatile metabolites, treatments inhibited 83% of Fov sporulation. In thermostable non-volatile metabolites, isolate 02 inhibited 50% of mycelial growth and 92% of Fov sporulation. In the mycoparasitism test, all isolates were efficient. The isolates inhibited from 65 to 100% of the germination of Fov conidia. For the sanity test, the treatments reduced the incidence of the pathogen in seeds by 98%. In terms of physiological quality, treatments with Trichoderma showed an increase in dead seeds. In the in vivo biological control, the treatment with the isolates reduced the rate of Fov infection, generated an increase in plant height, stem diameter, shoot and root dry matter and an improvement in chlorophyll (a) fluorescence. Treatment with Fov alone showed a negative correlation with photosynthesis variables in the main components. All isolates of Trichoderma spp. showed control of Fov in vitro. In terms of physiological quality, germination and emergence were compromised, but the incidence of pathogens associated with the seeds was reduced. The treatments with TH, TS and 729 allowed greater development of cotton plants, generating greater dry matter yield and functionality of the photosynthetic system and reduced the rate of Fov infection in plants